2010
DOI: 10.1242/jeb.042515
|View full text |Cite
|
Sign up to set email alerts
|

Insects running on elastic surfaces

Abstract: SUMMARY In nature, cockroaches run rapidly over complex terrain such as leaf litter. These substrates are rarely rigid, and are frequently very compliant. Whether and how compliant surfaces change the dynamics of rapid insect locomotion has not been investigated to date largely due to experimental limitations. We tested the hypothesis that a running insect can maintain average forward speed over an extremely soft elastic surface (10 N m−1) equal to 2/3 of its virtual leg stiffness (15 N m−1). Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 67 publications
3
66
0
Order By: Relevance
“…The small moment created by the rising arm of the backpack did not produce roll motions outside the range of those reported in previous experiments [5]. Backpacks were calibrated and accelerations were corrected for gravity using the kinematic tracking to define the relative orientation of the backpack with respect to the gravity vector at each point in time [46]. We off-loaded acceleration data from the backpack via an approximately 0.5 m tether of 50 mm wires attached to a data acquisition board (National Instruments, BNC 2090, Austin, TX, USA).…”
Section: Methods (A) Animalsmentioning
confidence: 95%
See 1 more Smart Citation
“…The small moment created by the rising arm of the backpack did not produce roll motions outside the range of those reported in previous experiments [5]. Backpacks were calibrated and accelerations were corrected for gravity using the kinematic tracking to define the relative orientation of the backpack with respect to the gravity vector at each point in time [46]. We off-loaded acceleration data from the backpack via an approximately 0.5 m tether of 50 mm wires attached to a data acquisition board (National Instruments, BNC 2090, Austin, TX, USA).…”
Section: Methods (A) Animalsmentioning
confidence: 95%
“…We placed retroreflective markers on five balsa wood arms projecting from the backpack and tracked them with high-speed videography at 500 fps (AOS Technologies AG, Switzerland). Fitting the five digitized points in a two-dimensional camera view to a geometric model of the arms' configuration enabled three-dimensional reconstruction of the animal's pitch, roll and yaw [46]. We report yaw velocity changes instead of yaw, because the cockroach's heading was not fixed within the arena and angular velocity was more comparable across trials.…”
Section: Methods (A) Animalsmentioning
confidence: 99%
“…However, when startled, even deafferented cockroaches were capable of sustaining a fast tripod trot. In addition, a body of literature shows that running cockroaches do not readily adapt their leg motions to the shape of the substrate (Jindrich and Full, 1999;Jindrich and Full, 2002;Sponberg and Full, 2008;Spence et al, 2010). In particular, it has been suggested that feedback is too slow to be useful to a sprinting animal, at least within a single stride .This distinction between the importance of afferent feedback in coordinating a slower gait and its apparent irrelevance to faster running could provide a simple explanation for our observations, and one that also resolves the dilemma of how a walking insect uses both CPGs and feedback in gait control.…”
Section: Gait Controlmentioning
confidence: 99%
“…Although spring-mass-like CoM motion was observed only in some of these studies (Ferris et al, 1998;Moritz and Farley, 2003;Spence et al, 2010), a common finding is that on non-solid surfaces, limbs do not necessarily behave like springs to save energy. In addition, these studies suggest that both the active control of body and limb movement through the nervous system and the passive mechanical responses of viscoelastic limbs and feet with the environment play important roles in the The zebra-tailed lizard [Callisaurus draconoides Blainville 1835; snout-vent length (SVL) ~10cm, mass ~10g; Fig.1A] is an excellent model organism for studying running on natural surfaces because of its high locomotor performance over diverse terrain.…”
Section: Introductionmentioning
confidence: 98%
“…Laboratory experiments have begun to reveal mechanisms of organisms running on non-solid surbstrates, such as elastic (Ferris et al, 1998;Spence et al, 2010), damped (Moritz and Farley, 2003), inclined (Roberts et al, 1997) or uneven (Daley and Biewener, 2006;Sponberg and Full, 2008) surfaces, surfaces with few footholds (Spagna et al, 2007) and the surface of water (Glasheen and McMahon, 1996a;Hsieh, 2003). Although spring-mass-like CoM motion was observed only in some of these studies (Ferris et al, 1998;Moritz and Farley, 2003;Spence et al, 2010), a common finding is that on non-solid surfaces, limbs do not necessarily behave like springs to save energy.…”
Section: Introductionmentioning
confidence: 99%